Between Microeconomics and Geopolitics: On the Reasonable Application of Competition Law. Issue 3 (26th October 2021) - Andriychuk, Oles
Abstract: For decades competition law was interpreted and applied through the prism of the economic analysis of law. This approach has advantages, enabling one to master both the methodological and normative features of the field. The use of economic rationality helps one to understand the motivation of market agents. The use of advanced mathematics allows robust modelling of the wide variety of empirical and theoretical factors. The use of efficiency and consumer welfare helps one to calibrate the goals of competition law. Such a 'standard' perception of the discipline, however, is in a deep crisis, and – as this article explains – chiefly for the right reasons. The conceptual divide between the representatives of Law and Economics and those adhering to a more societal account of competition law has many levels and dimensions. This article investigates the foundational aspect of the divide: the divergence in epistemic perception of legal and economic expertise.